Lego Media for Developing Fine Motor Skills of 4-5 Years Old Early Childhood at Ra (Islamic Kindergarten) Nurul Fata Sukahaji - Amelia, Eem; Purnamasari, Rika; Sijojudin, Habibah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
Children's motor skills are basic skills that must be developed early, especially fine motor skills. Fine motor skills are essential skills that must be mastered because they will support other developments. Fine motor skills development for early childhood should be taught through engaging in additional exercises. One is providing Lego media to stimulate fine motor skills development. Children must be attracted to fun media in their instructive cycle Hence, this research objective was to determine how developing fine motor skills using Lego media improves fine motor skills. This research used a quantitative experimental approach. The research population consisted of all students of RA Nurul Fata, totaling 36 children. The data collection techniques included interviews, observation, documentation, and checklists. The research results using the t-test on SPSS showed a significant effect on fine motor skills development after being given Lego media to children aged 4-6 at RA Nurul Fata.